Students' Perceptions of the Importance of Presentation Skills to Succeed in the Workplace - Bhattacharyya , Ena; SIVAPALAN, SUBARNA; Md Nordin, Shahrina (Universiti Putra Malaysia Press 2009, 2009)
Abstract: Oral communication is recognized as an essential element of the curriculum in technical disciplines. The engineering disciplines have also begun to explore the role of oral performance as both a learning tool and outcome. Students in this discipline are expected to be proficient both technically and communicatively. Research indicates that the engineering community, be it engineering educationists or professionals realize the importance of oral communication skills, specifically presentation skills, in developing competent engineers for the workplace. This research therefore seeks to investigate engineering students’ perceptions of the importance of presentation skills to succeed in an engineering based workplace. Feedback obtained from the students’ with regard to the importance of presentation skills will provide communication lecturers’ with a better understanding and insight of the needs and importance of presentation skills in the engineering industry for engineering students to succeed in the workplace.